Inventory management system for distributed stores / Melisa Sundram - Melisa , Sundram (2004)
Inventory Management System is an inventory management and organization tool for distributed chains stores that is stores at different locations under the same management. The management at the main office, supervisors and clerks at the chain stores are the main target of this system. The main purpose of IMS is to allow the main office to monitor the activities of the chain stores and to enable the management to make better business decisions and minimize risks based on the sales of its stocks at the chain stores. IMS would also enhance better communication and interaction between the chain stores and the management at the main office. The development model used to develop this system is the Waterfall with Prototyping model. This main reason for choosing this model is that the processes in the model can be tailored to meet the specific requirements but changes can stiU be made to the applications. The tools used to develop IMS comprise Visual Basic 6.0 and Microsoft SQL Server 2000 is chosen as Database Management System. Crystal Report is used as the report generating tool for the IMS system.